Dy-Modified Mn/TiO2 Catalyst Used for the Selective Catalytic Reduction of NO in Ammonia at Low Temperatures - Bing Xu; Zhen Wang; Jie Hu; Lei Zhang; Zhipeng Zhang; Hongtan Liang; Yong Zhang; Guozhi Fan (Molecules, 2024)
A novel Mn/TiO2 catalyst, prepared through modification with the rare-earth metal Dy, has been employed for low-temperature selective catalytic reduction (SCR) denitrification. Anatase TiO2, with its large specific surface area, serves as the carrier. The active component MnOx on the TiO2 carrier is modified using Dy. DyxMn/TiO2, prepared via the impregnation method, exhibited remarkable catalytic performance in the SCR of NO with NH3 as the reducing agent at low temperatures. Experiments and characterization revealed that the introduction of a suitable amount of the rare-earth metal Dy can effectively enhance the catalyst’s specific surface area and the gas–solid contact area in catalytic reactions. It also significantly increases the concentration of Mn4+, chemisorbed oxygen, and weak acid sites on the catalyst surface. This leads to a notable improvement in the reduction performance of the DyMn/TiO2 catalyst, ultimately contributing to the improvement of the NH3-SCR denitrification performance at low temperatures. At 100 °C and a space velocity of 24,000 h−1, the Dy0.1Mn/TiO2 catalyst can achieve a 98% conversion rate of NOx. Furthermore, its active temperature point decreases by 60 °C after the modification, highlighting exceptional catalytic efficacy at low temperatures. By doubling the space velocity, the NOx conversion rate of the catalyst can still reach 96% at 130 °C, indicating significant operational flexibility. The selectivity of N2 remained stable at over 95% before reaching 240 °C.